Implementasi Pembelajaran Daring Pada Masa Pandemi Covid-19 (Studi Kasus Di Kelas V SDN 3 Sila) Tahun Ajaran 2020/2021 - Maulana Al Awaludin; A Hari Witono; Itsna Oktaviyanti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2021)
The Covid-19 pandemic has created various kinds of changes in the state of society, especially in the world of education in Indonesia. One of these changes is the replacement of the face-to-face teaching and learning process (KBM) into the application of an online learning system. This study aims to 1) describe the implementation of bold learning during the Covid-19 pandemic at SDN 3 Sila. 2) to find out the obstacles and obstacles experienced in implementing online learning. This study uses a case study qualitative method using data collection techniques used are observation, interviews, and documentation. Data analysis by reducing data, presenting data, and drawing conclusions. The results of this study indicate that: 1) the implementation of online learning which is applied to V by using several applications that support the implementation of learning and remains guided by the design of the implementation of learning that has been made as well as developing and assessing student learning outcomes based on assignments, repetition, and activity during learning. 2) inhibiting factors and obstacles in the implementation of learning, namely the limitations of supporting facilities, lack of effective learning management, things that are felt to be not optimal and lack of parental supervision and assistance during learning activities carried out by students.